Data mining trends and applications in criminal science and investigations - Isafiade, Omowunmi E., 1982-; Bagula, Antoine B., 1960-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book presents scientific concepts and frameworks of data mining and analytics implementation and uses across various domains, such as public safety, criminal investigations, intrusion detection, crime scene analysis, and suspect modeling"--Provided by publisher.
On the advancement of using data mining for crime situation recognition: a comparative review / Omowunmi E. Isafiade, Antoine Bagula, Sonia Berman -- A classification framework for data mining applications in criminal science and investigations / Mahima Goyal, Vishal Bhatnagar, Arushi Jain -- Visual analytics for crime analysis and decision support / Chih-Hao Ku, Alicia Iriberri, Goutam Jena -- Crime hotspot detection: a computational perspective / Emre Eftelioglu, Shashi Shekhar, Xun Tang -- Visual data mining: a great opportunity for criminal investigation / Mehrdad Ghaziasgar [and 3 others] -- On the Use of Bayesian network in crime suspect modelling and legal decision support / O. E. Isafiade, A. B. Bagula, S. Berman -- Forensic investigation of digital crimes in healthcare applications / Nourhene Ellouze, Slim Rekhis, Noureddine Boudriga -- Data mining analytics for crime security investigation and intrusion detection / Boutheina Fessi, Yacine Djemaiel, Noureddine Boudriga -- Automated identification of child abuse in chat rooms by using data mining / Mohammadreza Keyvanpour [and 4 others] -- Data mining techniques for distributed denial of service attacks detection in the internet of things: a research survey / Pheeha Machaka, Fulufhelo Nelwamondo.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 07/07/2016).
Keywords: Criminal investigation -- Data processing; Data mining; Crime analysis; Crime mapping; Crime suspect monitoring; Cyber crime; Data analytics; Forensic investigations; Visual data mining; Electronic books